Association of patients' knowledge on the disease and its management with indicators of disease severity and individual characteristics in patients with Chronic Obstructive Pulmonary Disease (COPD): results from COSYCONET 2 - Fischer, Carolina; Siakavara, Maria; Alter, Peter; Vogelmeier, Claus F.; Speicher, Tim; Pott, Hendrik; Watz, Henrik; Bals, Robert; Trudzinski, Franziska; Herth, Felix; Ficker, Joachim H.; Wagner, Manfred; et al. (Patient preference and adherence, 2024)
Background: In patients with chronic diseases, including those with chronic obstructive pulmonary disease (COPD), knowledge on the disease and its self-management is considered as relevant for improving disease control and long-term outcome. We studied to which extent components of knowledge depended on potential predictors, such as participation in educational programs and disease severity. For example, the perception of exacerbations or GOLD grade might modulate the content and reliability of COPD understanding. Methods: Data from the German COSYCONET 2 COPD cohort was used, and 13 questions addressing knowledge and self-management were analyzed. Results: Overall, 310 patients with the diagnosis of COPD of GOLD grades 1/2/3/4 as well as the former grade 0 were included (39.7% female, median age 66.0 years). The answers to 3 questions (knowledge of term exacerbation, pursed lip breathing technique, criteria for contacting a doctor) were improved (p < 0.05 each) when patients had had moderate-to-severe exacerbations, and to one question (breathing exercise) when having COPD grade 3/4 versus 0/1/2. The other 9 responses did not depend on disease severity, but most of the knowledge was improved when having participated in an educational COPD program. This was particularly true for knowledge that also depended on exacerbations, or if the treating physician was a pulmonary specialist. In some responses, the proportion of correct answers was significantly reduced in males compared to females. The dependence on education level, existence of a treatment plan, self-reported level of risk aversion and low depression score was weak and heterogeneous. Conclusion: These findings suggest that part of the disease-related knowledge in patients with COPD was reinforced by the experience of exacerbations, especially knowledge regarding criteria on contacting a physician. These observations might help in focusing education on those parts of knowledge that are considered as important by patients based on their own experience.$534